Dermatitis herpetiformis - Emy Abi Thomas (Wolters Kluwer Medknow Publications, 2014)
Dermatitis herpetiformis (DH) is an uncommon condition. We describe a young boy who presented with pruritic, recurrent grouped fluid filled and papular lesions over the body. DH was confirmed by histopathological examination of the vesicle.